Local Policy Choice: Theory and Empirics - David R. Agrawal; William H. Hoyt; John D. Wilson (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper critically surveys the growing literature on the policy choices of local governments. First, we identify various reasons for local government policy interactions, including fiscal competition, bidding for firms, yardstick competition, expenditure spillovers, and Tiebout sorting. We discuss theoretically what parameters should be estimated to determine the reason for competition among local governments. We emphasize how the policy outcomes emerging from this competition are affected by the presence of constraints imposed by higher-level governments. Second, we integrate theoretical and empirical analyses on the effects of fiscal decentralization on mobility, spillovers, fiscal externalities, economic outcomes, and distributional issues. Third, we identify key issues that arise in the empirical estimation of strategic interactions among local governments and highlight recent quasi-experimental evidence that has attempted to identify the mechanism at work. Finally, a synthesis model, containing multiple mechanisms and fiscal instruments, resolves some puzzles and provides guidance for future research.
Keywords: H20; H40; H70; R50; 330; fiscal competition; yardstick competition; spillovers; strategic policy; interdependence; reaction functions; local public finance